Approaches review and tools analysis for thermal processes modeling in electron beam welding. Issue 5 (November 2020) - Milov, A V; Tynchenko, V S; Kurashkin, S O; Petrenko, V E
Abstract: The article is devoted to a review of approaches used to simulate thermal processes occurring during electron beam welding of thin-walled products. The analysis of more than fifty sources is carried out on the basis of which ideas about the current state of the problem considered in the article are formed. To implement the simulation, it is possible to use modern software systems such as: ANSYS, Comsol Multiphysics, Abaqus and NX Nastran, each of which has its own set of advantages and disadvantages. By using the method of expert evaluation on the basis of the formulated criteria, the most effective software was selected. The results of the study of mathematical models implemented in the selected software system will allow not only to get an idea of the thermal process occurring during electron beam welding of thin-walled products, as such, but also to form a mathematical justification for making technological and control decisions.